The Correlation between Quality of College Life and Academic Hardiness on College Students (Retracted) - Aprodita, Nindya Putri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2020)
This research aims to understand how students’ quality of college life and their academic hardiness is related. The research used a quantitative method with a correlational approach. The measuring instrument used is an adaptation of the QCL Measure by Sirgy (2007) and the Academic Hardiness Scale by Benishek (2005). The sample of this research consists of 89 people who are Psychology students from a private university in Jakarta. This research showed that the quality of college life has a significant relation with academic hardiness. Based on this research, it is suggested that education institutions enforce the quality of college life aspect that has the strongest relation with academic hardiness, which is the academic aspect. This academic aspect encompasses the quality of lecturers, learning atmosphere, and quality of learning materials.